Cinética ruminal in vitro de silagens de aveia branca com diferentes teores de matéria seca inoculadas com aditivo microbiano-enzimático - Prestes, Ana Carolina Gonçalves (2021)
The use of silage for conservation the forage is widely used in a time of forage emptiness. The white oat is a culture adapted to cold weather, then it is a forage option to be ensiled at that time. The use of silage additives acts to reduce the pH by multiplying lactic acid bacteria, providing desirable and more efficient fermentation of the silage. The objective of this project was evaluate the ruminal kinetic in vitro of white oat silages inoculated with microbial and enzymatic additives. The work was conducted in Food Analysis Laboratory of the Universidade Tecnológica Federal do Paraná, Câmpus Dois Vizinhos. The oat culture was implanted in the month of May 2019 and the ensiling realized inthe month of July 2019, at two stages of maturation, with 23 and and 28% DM and then storedin micro silos with five levels of the additive (0, 500, 1000, 1500 e 2000 mg/kg MV). The opening of micro silos ocurred after 42 days of fermentation, and sample were collected to proceed with theincubation of the material for in vitro analysis. Was evaluated parameters of kinetic of ruminal degradation in vitro: latency time (lag time), accumulated gas volume and degradation rate, for a period of 144 hours of in vitro incubation in the differente treatments and was estimated through the procedure of nonlinear model, using a unicompartmental mathematical model. White oat silage with 23% DM showed higher in vitro gas production volume, while the addition of the microbial-enzyme inoculant increased the in vitro gas production rate and decreased the half-life time of the silages. The highest in vitro gas production rate and shortest half-life time of silages could be obtained with the doses of 774.43 kg/t-1 MV and 756.30 kg/t-1 MV of the inoculant, respectively.